The Ideas of David Hume (1711-1776) in the Development of Psychology and Multicultural Education - Sairah, Abdul Rokhmat (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Education needs a psychological approach to its process and mechanism. Contemporary psychology is rooted in philosophical thought and physiological inquiry. Psychology cannot be separated from the influence of three schools in philosophy, i.e., materialism, empiricism, and positivism. One of the empiricist thinkers who gave nuances and color in the development of psychology was David Hume (1711-1776). This article aims to reveal David Hume's thoughts, which provided motives in the development of psychology. This article is the result of research to develop a historical and philosophical theory of psychology. This research aims to investigate the background of the emergence of psychology from David Hume's thoughts. The focus of this research is to survey the influence of David Hume's empiricism on the development of psychology. The research method employed in this study is philosophical hermeneutics with synchronic and diachronic interpretations of David Hume's thoughts. As a qualitative study, the relevant data of the study was collected from various sources both primary and secondary. The primary literature used is texts on the history of psychology and David Hume’s works. The secondary sources for this research are various comments on Hume's thoughts and general psychology texts. The results of this research can be used as a reference in learning related to the history and philosophy of psychology. This article presents Hume's thoughts in the search for human nature along with the methodological principles he developed, which inspired scientists after Hume, as well as the influence of his thoughts on the progress of experimental psychology, which continues to develop, in giving a pattern to contemporary psychology